STATISTICAL ANALYSIS OF ECONOMIC STATE OF POPULATION EMPLOYMENT AND CHANGES IN IT - Ayubjonov Abbos Hosilovich (Bright Mind Publishing, 2025)
In order to further improve the field of statistics in Uzbekistan, it is necessary to form a system that comprehensively reflects the state and development of the country's economy at the macro, meso and micro levels of employment by types of economic activity, combines statistical indicators obtained from various sources into meaningfully coherent groups, increases the reliability and validity of their intercomparison, and makes decisions on the development of regions based on the data of this system.
Keywords: New Uzbekistan, National Statistical System, improvement, labor, employment, population welfare, standard of living, poverty, economy.